2010
DOI: 10.2460/javma.236.11.1221
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urine protein-to-creatinine ratio in urine samples collected by cystocentesis versus free catch in dogs

Abstract: The UPC ratio in dogs was minimally affected in urine samples collected by free catch, thus allowing correct grading of proteinuria with this method. The high reliability of the UPC ratio in free-catch urine samples coupled with the ease of collection should increase the use of this value for assessment of proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 11 publications
5
47
1
2
Order By: Relevance
“…Possibly, with higher UPC values, a larger mean absolute difference could have been observed. These findings are consistent with previous studies in 81 dogs and 43 cats, which revealed that UPC may be reliably measured in free catch urine samples . The largest absolute differences occurred in dogs with overt proteinuria and were not associated with a change in classification across proteinuria categories.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Possibly, with higher UPC values, a larger mean absolute difference could have been observed. These findings are consistent with previous studies in 81 dogs and 43 cats, which revealed that UPC may be reliably measured in free catch urine samples . The largest absolute differences occurred in dogs with overt proteinuria and were not associated with a change in classification across proteinuria categories.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical importance of borderline proteinuria in dogs still needs to be elucidated. In the authors' and others' experience, cystocentesis samples are mentioned to be more reliable for UPC measurement, but this is not well documented . However, because of possible drawbacks such as appropriate immobilization of dog and localization of bladder, risk for laceration, hematuria, or owner noncompliance, cystocentesis is often not performed in clinical practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quando a proteinúria está associada à grande quantidade de células inflamató-rias, é difícil certificar-se da origem da proteinúria (Hardy & Osborne 1974). Porém, o estudo realizado por Beatrice et al (2010), assim como no estudo de Maddens et al (2010), a bacteriúria não foi relacionada à alterações nos valores da relação proteína/creatinina. Neste estudo, não foi realizada a análise do sedimento urinário, o que pode comprometer a proposta de origem renal para as alterações da relação proteína/creatinina.…”
Section: Discussionunclassified
“…In healthy dogs, voided urine or urine collected by cystocentesis may be used for UPC measurement 17. In practice, owners frequently are asked to collect urine at home and bring the sample to a veterinary hospital for analysis.…”
Section: Introductionmentioning
confidence: 99%